A Study on Clinical Pro?le, Risk Factors, Angiographic Pro?le and Short-Term Mortality of Acute Coronary Syndrome in Smokers vs Non Smokers - Reddy, B V Narayana; Korrapati, Hemasundar; Chegireddy, Supraja (Asian Journal of Medical Research, 2020)
Background: Smoking has long been positively associated with the development and progression of coronary heart disease. However, lon- gitudinal cohort studies evaluating smoking habits among cardiac patients as well as the role of socio-demographic factors determining such behaviours are scarce and have been focused on primary care practice. Prevalence of acute coronary syndrome in young individuals is increasing progressively. Previous studies have focused on the analysis of risk factors and to some extent coronary angiographic profile in smokers vs non-smokers patients with acute coronary syndrome. The aim of the study is to study the acute coronary syndrome in smokers versus non-smokers and to analyse with respect to baseline characteristics. Subjects and Methods: It was a prospective study conducted at Department of Cardiology, Katuri Medical College & Hospital Guntur. Results: In the present study, Acute coronary syndrome occurred seven years earlier in smokers compared with non-smokers (p<0.05) Smokers were frequently male subjects compared with non-smokers (p<0.001) Smokers had a lower prevalence of Diabetes compared with non-smokers (p<0.001) Smokers had a higher prevalence of Obesity compared with non-smokers (p<0.001). Smokers presented with more acute infarctions and less Unstable angina compared with non-smokers (P<0.001). Conclusion: In the present study, significant differences were observed in coronary risk factor profile between smokers and non-smokers patients with STEMI and NSTEMI/UA. Larger studies will be required to establish specific associations between presentation of acute coronary syndromes and angiographic profiles in smokers.